Influence of serially developed two stenoses on flow characteristics of Jeffrey fluid flow through an artery - Sangita S. Mahajan; Veena B. S. (Cogent Engineering, 2025)
The study of hemodynamics of fluid flow through an artery with serially developed stenoses is significant as stenosis affects key flow characteristics. The aim is to investigate the combined effect of non-Newtonian behavior and serially developed arterial stenoses on physiologically important blood flow characteristics. The blood flow is through a uniform cross-sectioned cylindrical artery with stenoses of different shapes occurring in sequence, the first being cosine and the second bell-shaped. The study primarily investigates the changes in key characteristics wall shear stress and blood flow resistance. A novel mathematical model is developed with the above mentioned characteristics by considering moderate stenoses, and analytical expression for important blood flow characteristics, such as velocity, volumetric flow rate, wall shear stress, and resistance to flow, are obtained. The effects of different parameters, namely, stenosis severity, shape parameter, and Jeffrey parameter on flow characteristics across the stenotic region are discussed using graphs. The upsurge in Jeffrey parameter decreases wall shear stress significantly; resistance to flow is significantly affected by height of stenosis. It is observed that flow resistance increases by 146% as stenosis progresses from 60% to 70% and when the stenosis height reaches 80%, resistance to flow rises by 279%. Also, as stenosis height increases from 50% to 60%, wall shear stress at the throat rises by 95.3% and when the stenosis height increases further from 60% to 70%, wall shear stress increases by 137%. Results indicate a positive correlation between Jeffrey fluid parameter and blood fluidity in diseased conditions.